2011
DOI: 10.1016/j.adolescence.2011.07.007
|View full text |Cite
|
Sign up to set email alerts
|

The role of ecological assets in positive and problematic developmental trajectories☆

Abstract: Two theoretical perspectives have been proposed to describe, explain, and intervene in adolescent development – prevention science and positive youth development (PYD). An integrative model bridging these two perspectives posits that it is important to assess the extent to which the same, similar, or complementary mechanisms may be responsible for preventing problem behavior and promoting PYD. Therefore, using data from the 4‐H Study of PYD, the present study examines the role of assets in the family, school, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 71 publications
(120 reference statements)
1
25
0
2
Order By: Relevance
“…Dentre os diversos aspectos que cercam a gestão de um programa social, é fundamental garantir um processo de avaliação capaz de alcançar seus múltiplos níveis ecológicos 24 e que seja confiável, teórico e metodologicamente 27,36 . De forma que o processo de avaliação possa sustentar as evidências do alcance dos seus objetivos e as decisões que serão desencadeadas a partir dos seus resultados.…”
Section: Discussionunclassified
“…Dentre os diversos aspectos que cercam a gestão de um programa social, é fundamental garantir um processo de avaliação capaz de alcançar seus múltiplos níveis ecológicos 24 e que seja confiável, teórico e metodologicamente 27,36 . De forma que o processo de avaliação possa sustentar as evidências do alcance dos seus objetivos e as decisões que serão desencadeadas a partir dos seus resultados.…”
Section: Discussionunclassified
“…To understand how regulation in response to phenomena outside the learning task (e.g., unstable home environment) influences SRL, we pose an integrated model of SRL (iSRL) that demonstrates how all SRL processes occur within a hierarchically nested context. This hierarchical structure is best understood through an ecological assets perspective (Bowers et al 2011;Bronfenbrenner 1977;Bronfenbrenner and Ceci 1994). In the iSRL model, we demonstrate how self-regulatory capacity is limited via depletion (e.g., ego depletion; Schmeichel and Baumeister 2004), extending the notion that SRL is a finite capacity (Winne 2010) beyond the immediate learning task and context, as described below.…”
Section: Incorporating Social and Clinical Psychological Lenses To Brmentioning
confidence: 99%
“…composition of essays by hand, with a typewriter, using word processing software). Intermediate influences include individuals and environments within the concentric circles like one's city, neighborhood, and family (Bowers et al 2011;Bronfenbrenner 1977;Bronfenbrenner and Ceci 1994). These factors have independent influence on the individual, and can also mediate the effects of other factors.…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…CTC is a strengths-based approach to social work practice (Haggerty & Shapiro, 2013) that uses a risk and protective paradigm (Coie et al, 1993; Pollard, Hawkins, & Arthur, 1999) to identify individual and environmental strengths. Studies have identified protective factors in the individual, peer, family, school, and community domains shown to decrease the likelihood of problem behaviors and/or mitigate the effects of risk exposure (Bowers et al, 2011; Losel & Farrington, 2012). …”
Section: Protective Factorsmentioning
confidence: 99%